Spectrum and energy of the Sombor matrix - Gutman, Ivan (Vojnotehnički glasnik / Military Technical Courier, 2021)
Introduction/purpose: The Sombor matrix is a vertex-degree-based matrix associated with the Sombor index. The paper is concerned with the spectral properties of the Sombor matrix.Results: Equalities and inequalities for the eigenvalues of the Sombor matrix are obtained, from which two fundamental bounds for the Sombor energy  (= energy of the Sombor matrix) are established. These bounds depend on the Sombor index and on the „forgotten“ topological index.Conclusion: The results of the paper contribute to the spectral theory of the Sombor matrix, as well as to the general spectral theory of matrices associated with vertex-degree-based graph invariants.
Keywords: Sombor matrix; Sombor energy; Sombor index; vertex-degree-based graph invariant; spectrum (of matrix)